Hybridization and hybrid speciation under global change. Issue 4 (23rd May 2016) - Vallejo‐Marín, Mario; Hiscock, Simon J.
Summary: An unintended consequence of global change is an increase in opportunities for hybridization among previously isolated lineages. Here we illustrate how global change can facilitate the breakdown of reproductive barriers and the formation of hybrids, drawing on the flora of the British Isles for insight. Although global change may ameliorate some of the barriers preventing hybrid establishment, for example by providing new ecological niches for hybrids, it will have limited effects on environment‐independent post‐zygotic barriers. For example, genic incompatibilities and differences in chromosome numbers and structure within hybrid genomes are unlikely to be affected by global change. We thus speculate that global change will have a larger effect on eroding pre‐zygotic barriers (eco‐geographical isolation and phenology) than post‐zygotic barriers, shifting the relative importance of these two classes of reproductive barriers from what is usually seen in naturally produced hybrids where pre‐zygotic barriers are the largest contributors to reproductive isolation. Although the long‐term fate of neo‐hybrids is still to be determined, the massive impact of global change on the dynamics and distribution of biodiversity generates an unprecedented opportunity to study large numbers of unpredicted, and often replicated, hybridization 'experiments', allowing us to peer into the birth and death of evolutionary lineages.   Contents     Summary 1170 I. Introduction 1170 II. Hybrid formation 1172 III. Hybrid establishment: overcoming intrinsic and extrinsic post‐zygotic barriers 1175 IV. Outcomes of hybridization 1180 V. Outlook 1183   Acknowledgements 1184   References 1184